Ciclo biológico y hábitos de colaspis submetállica jacoby col: chrysomelidae - Gualán Vega, John Patricio (2013)
In the present research work is study the life cycle and host of Colaspis submetállica J., significant pest in banana cultivation. . It was found that embryonic period lasts an average of 6.9 days and 19.75 for the larval period, while the 8.9 pupal stages, completing its full cycle in 39.6 days. Their larvae are quite agile, have not fulfilled their curvature and roots of Poaceae cycle as Paspalum conjugatum, Eleusine Indica and Mussa sapientum, choosing soft and succulent tissues in the first larval instar. Their eggs are laid singly or in groups a few inches into the soil, in this research were more preference in place on decaying remains of trees. Insect adults are nocturnal, finding them in the day in the flag leaf of the banana plant and as well as the children of water in its inflorescence bracts deployed in small cracks in the floor, fingers tender detached when work is performed deschive; this research found feeding in the night hours Pilgrim (Hibiscus sp.).